2 A history of the 'paediatric bipolar disorder' epidemic: driving forces, iatrogenic consequences and lessons for psychiatric nosology. (4th December 2019) - Parry, Peter
Abstract : Background: 'Paediatric bipolar disorder' (PBD) is a controversial diagnosis that began in the mid-1990s when several US child psychiatric researchers hypothesised that atypical mania commonly occurred among prepubertal children in the form of chronic irritability or ultradian cycling (several mood episodes per day). PBD was rapidly translated into clinical practice in the US. Large numbers of prepubertal children were treated with second-generation antipsychotics (SGAs). A highly cited meta-analysis of epidemiological community prevalence studies of paediatric psychiatric disorders claimed a worldwide prevalence of 1.8%, later updated to 2.06%. Research and media reports indicated likely considerable iatrogenic morbidity and mortality. Concerns of overdiagnosis and failure to address contextual factors such as childhood maltreatment were expressed in the literature and media. Objectives: To assess: 1) the validity of the PBD hypotheses, 2) factors that drove the PBD epidemic, 3) iatrogenic consequences and 4) implications for psychiatric nosology. Method: Review academic literature, media and grey literature; survey of Australasian child and adolescent psychiatrists; re-examination of original epidemiological studies from which the claims of high community prevalence were derived; use of bibliometric analyses to examine the PBD literature for geographic spread of the PBD hypothesis and presence/absence of reference to contextual factors such as attachment, trauma and maltreatment. Results: Five of six international longitudinal high-risk offspring studies supported the classical view that mania almost never presents before mid-adolescence. Internal pharmaceutical company documents revealed intent to expand bipolar disorder diagnoses to support market growth for SGAs including to children. Diagnosis upcoding aspects of the US health system and a biomedical reductionist paradigm within psychiatry that neglects contextual factors in child development helped drive the epidemic. Clinical diagnostic prevalence of childhood bipolar disorder was 100- to 900-fold higher in the USA than in Australasia or Europe. Australasian child and adolescent psychiatrists were sceptical of the PBD hypothesis. Community epidemiological rates of bipolar disorder were near zero if parent-child concordance was required. The pro-PBD literature was affiliated with a sizeable minority of mostly US academic institutions and there was limited reference to contextual factors such as attachment, trauma and maltreatment. Conclusions: The PBD epidemic of the past two decades occurred within a biomedical reductionist paradigm. It was mostly confined to the USA and driven by research from several academic institutions often with pharmaceutical industry support. Psychiatric nosology, particularly in child and adolescent psychiatry, needs to be based in developmental psychology, the biopsychosocial model and awareness of the effects of trauma and maltreatment.